2000
DOI: 10.1007/s002040050658
|View full text |Cite
|
Sign up to set email alerts
|

Effects of xenoestrogen bisphenol A on uterine and pituitary weight, serum prolactin levels and immunoreactive prolactin cells in ovariectomized Wistar rats

Abstract: Considerable attention has currently been focused on bisphenol A (BPA), an environmental endocrine disrupting chemical that has oestrogenic activity. In vitro and in vivo short-term assays have shown that BPA is weakly estrogenic. In addition, the issue of species- and strain-differences in susceptibility to BPA was raised. The treatment of ovariectomized (OVX) Wistar rats with BPA at doses of 11-250 mg/kg per day, s.c., for 7 days, resulted in significant dose-dependent regrowth of uterus in uterotrophic assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 43 publications
0
27
0
4
Order By: Relevance
“…They reported that BPA exhibited uterotrophic responses in 3-day uterotrophic assay using immature rats only at higher dosage (400 mg/kg/day, oral and s.c.). However, Goloubkova et al (2000) showed that the treatment of OVX Wistar rats with BPA at doses of 11-250 mg/kg resulted in significant dose-dependent uterus regrowth. We predict that the OVX rat might be more sensitive to estrogenic responses than immature rats in uterotrophic assay for BPA.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that BPA exhibited uterotrophic responses in 3-day uterotrophic assay using immature rats only at higher dosage (400 mg/kg/day, oral and s.c.). However, Goloubkova et al (2000) showed that the treatment of OVX Wistar rats with BPA at doses of 11-250 mg/kg resulted in significant dose-dependent uterus regrowth. We predict that the OVX rat might be more sensitive to estrogenic responses than immature rats in uterotrophic assay for BPA.…”
Section: Discussionmentioning
confidence: 99%
“…BPA induced prolactin (PRL) release in vitro 4,5) . It also increased uterine and pituitary weight, the serum PRL level and the number of immunoreactive PRL cells in ovariectomized Wistar rats 6) . Reproductive toxicity of BPA has been reported in mice and rats.…”
mentioning
confidence: 84%
“…4.2.1 Female 4.2.1.1 Rat: Goloubkova et al (2000), supported by the Brazilian National Council of Scientific and Technological Development and the National University of Rio Grande Do Sul, examined the effects of bisphenol A exposure on the uterus and pituitary of ovariectomized rats. Wistar rats (60-67 days old) were fed a standard certified rodent diet.…”
Section: Experimental Animalmentioning
confidence: 99%